2021
DOI: 10.3389/fpsyg.2021.585477
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Pilot Study on Choking Episodes in Archery

Abstract: The aim of our study is to test the fit of an explanatory model of the frequency of the phenomenon of choking under pressure in archers, focusing on both the individual components (anxiety, coping styles, and decentralization) and environmental components (perception of coach assistance). 115 competitive athletes including 72 males (62.6%) and 43 females (37.4%) participated in the study, with average age of 39 years (±15.47). Participants reported personal data and completed measures of self-consciousness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 67 publications
0
22
0
2
Order By: Relevance
“…There are many different strategies for controlling emotions, but cognitive reappraisal is a significant and useful one [ 37 , 47 , 48 ]. According to studies, suppression of expression is not positively correlated with motor performance, whereas positive cognitive reappraisal is [ 14 ]; this boosts athletes’ feelings of fulfillment and enhances their performance on experimental tasks [ 15 ]. In addition, the cognitive reappraisal of emotions is often associated with positive aspects of the athlete’s well-being [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different strategies for controlling emotions, but cognitive reappraisal is a significant and useful one [ 37 , 47 , 48 ]. According to studies, suppression of expression is not positively correlated with motor performance, whereas positive cognitive reappraisal is [ 14 ]; this boosts athletes’ feelings of fulfillment and enhances their performance on experimental tasks [ 15 ]. In addition, the cognitive reappraisal of emotions is often associated with positive aspects of the athlete’s well-being [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…People may be able to relate to events more objectively, which could help them avoid becoming overly mentally and emotionally involved [ 12 ], and thus help them recognize unpleasant emotions that need to be controlled more quickly [ 13 ]. Other research has shown that positive cognitive reappraisal increases the feelings of positive emotions in archery athletes and enhances performance in experimental tasks [ 14 , 15 ], while expression suppression does not increase motor performance in table tennis [ 16 ]. Arousal reappraisal also helps golfers avoid “choking”, and to some extent, it ensures performance in putting tasks, similarly to cognitive reappraisal [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering burnout, in general, the athletes in the present study had low scores, similar to other individual sports, such as tennis ( Casagrande et al, 2014 , 2017 ), and other contact sports, such as rugby ( Cresswell and Eklund, 2005 ; Hodge et al, 2008 ). In sport psychology, it has been argued that burnout is more common in individual sports than in team sports, due to the higher levels of strength and time demands required ( Smith, 1986 ; Coakley, 1992 ; Diotaiuti et al, 2021a ). However, in the study of Gustafsson et al (2007) , higher burnout was found in male team sports athletes on the physical and emotional exhaustion and sports devaluation subscales, although the moderate to low effect size limits the scope of inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes, having to manage the times and methods of execution of the technical/athletic gesture, look for programs and technologies that accurately and thoroughly improve their performance ( Lange-Smith et al, 2023 ). An example is given by sports such as archery or shooting where the management of arousal turns out to be a fundamental aspect for dealing with physiological and behavioral conditioning coming from internal and external responses which influence performance ( Marzbani et al, 2016 ; Mikicin et al, 2018 ; Diotaiuti et al, 2021c ).…”
Section: The Integrated Bf + Nf Approachmentioning
confidence: 99%